Shielding reduced incidence of COVID-19 in patients with inflammatory arthritis but vulnerability is associated with increased mortality - Roxanne Cooksey (Rheumatology, 2022)
ObjectivesInvestigate whether individuals with inflammatory arthritis (IA), their treatments and shielding status affect the risk of adverse outcomes from COVID-19 for the entire population of Wales, UK.MethodsRetrospective, population-based cohort study using linked, anonymized electronic health data from SAIL Databank, including primary/secondary care, rheumatology, Office for National Statistics Mortality and COVID-19 laboratory data. Individuals aged 18 years and over testing positive for COVID-19 between March 2020 and May 2021 with READ Codes present for rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis formed the study cases.ResultsA total of 1966 people with IA and 166 602 without tested positive for COVID-19. The incidence rate was 3.5% (1966/56 914) in IA, vs 6% in the general population (166 602/2 760 442), (difference: 2.5%, 95% CI: 2.4%, 2.7%, P ≤0.001). In an adjusted Cox proportional hazard model, IA was not associated with higher mortality (HR: 0.56, 95% CI: 0.18, 1.64, P=0.286). Significant risk factors included shielding (HR: 1.52, 95% CI: 1.40, 1.64, P ≤0.001), hospitalization for previous infections (HR: 1.20, 95% CI: 1.12, 1.28, P ≤0.001), hospitalizations one year pre-pandemic (HR: 1.34, 95% CI: 1.25, 1.44, P ≤0.001) and glucocorticoid use (HR: 1.17, 95% CI: 1.09, 1.25, P ≤0.001).ConclusionsIndividuals with IA had a lower incidence of COVID-19, probably due to shielding. IA was not associated with increased mortality following COVID-19 infection; being vulnerable (shielded), comorbidities and other factors were associated with increased risk. These key risk factors can identify individuals with IA at greater risk from COVID-19 and advised to shield during high community prevalence.